Getting Shariah Brandmark: Strategy And Management Promotion of Cordova Hotel in Accelerating the Image as a Shariah Hotel - Rifqi Maulana Mansur (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purposes:. The purpose of this study was to determine the governance process of Cirebon Cordova hotel, the Cirebon promotional strategy of the Cordova hotel and how the governance & promotion strategy of the Sharia Cordova hotel image of Cirebon.Design/Methodology/Approach: The research method used in this study is to use analysis with an inductive approach, processes and meanings from a subject perspective that are more highlighted or can be referred to as descriptive qualitative research. The technique of collecting data uses observation, documentation, and interviews. The data is validated using the triangulation method. Data analysis techniques using data reduction, data presentation, and research / verification conclusions.Findings: The results of this study in the governance of the Cirebon Cordova Hotel use the Sharia concept, which is realized to provide the best comfort, security and service. The promotion strategy of the Cordova Cirebon hotel uses social media and print media and collaborates with travel services. The governance carried out by the Cirebon Cordova hotel already uses sharia principles, as evidenced by applying sharia concepts such as the rules applied in guest services that violate the opposite sex who are not muhrim, violations do not carry items that are prohibited according to Islamic and state religious rules. The Cirebon cordova hotel promotion strategy is carried out to do ethics & honesty in communicating product offerings to hotel visitors. To improve the image of Sharia Hotel, Cordova Hotels always recite the verses of the Holy Qur'an, prayer and do not provide entertainment facilities that cause disobedience such as discotheques, clubs, bars and gambling.Originality/Value: The article offers a new evidence of how a hotel endeavors in getting shariah image. Appealingly, the study can deeply describe the strategy and management promotion in reaching that reputation.